Dynamic Control of Ultrathin Electromagnetic Absorber Using Active High Impedance Metasurfaces - Wei, Zeyong; Li, Hongkun; Xu, Weijie; Cao, Yang (Frontiers in Physics, 2021)
In recent years, active metasurfaces have induced more interests, which provides great freedom of wave manipulation and gives rise to many novel phenomena. High impedance metasurfaces are a kind of artificial structures characterized by the in-phase reflection at the resonant frequency. It works as a magnetic mirror and can be applied in subwavelength cavity, low profile reflector antenna, etc. When introduce in tunable components, it possesses versatile functionalities and broader application. In this paper, we proposed an active high impedance metasurface which exhibits highly efficient absorption to the electromagnetic incidence. As an array of diodes are loaded between the gap of periodic gratings and applied with positive bias, the absorption frequency can be dynamically controlled by the level of bias voltage. At the resonant frequency, the reflection from the metasurface can be less than 1%, implying that most of the incidence is absorbed by the magnetic resonance of high impedance metasurface. When the bias voltage is tuned from 0V to +1.33V (the forward voltage), the resonant peak rises from 8.5GHz to 9.1GHz, providing a flexible control of electromagnetic wave absorption in X band.